Effects of different types of ginseng on intercellular wireless communication networks and central carbon metabolism pathways - Yujiao Liu; Dingqiang Lu; Jiayi Qiang; Lianjie Xu; Ming Li; Xinqian Wang; Yixuan Liu; Yifei Zhang; Wei Xu; Chenyu Xu; Qingwei Song; Wenling Wu; et al. (Journal of Future Foods)
Ginseng has high medicinal value. Different ginseng have different benefits, but how they work in the body's immune metabolism is unclear. In this study, different types of ginseng were ingested and serum cytokines, some metabolite concentrations and metabolic enzyme expression levels were measured. Intercellular communication networks and metabolic networks were constructed and analyzed for correlation. The results show that the effect of wild ginseng on cytokine secretion and metabolic pathway fluxes was greater. An intake of garden ginseng activated aerobic glycolysis to enhance immunity, while an intake of forest ginseng and wild ginseng increased pentose phosphate pathway, tricarboxylic acid cycle, and oxidative phosphorylation activity to promote immunity. Therefore, the intake of 500 mg/person of forest ginseng or 100 mg/person of wild ginseng was beneficial to health. The study of cytokines and metabolic networks may also provide new ideas for exploring the effects of ginseng and others on the body.